Isaiah in context: studies in honour of Arie van der Kooij on the occasion of his sixty-fifth birthday - Meer, Michaël N. van der; Meer, Michae͏̈l Nicolaas van der; Kooij, Arie van der; Keulen, Percy S. F. van; Peursen, Willem Th. van; Haar Romeny, Robert Barend ter (Vetus Testamentum / Supplements, 2010)
The present volume contains a collection of essays on the Book of Isaiah offered as a tribute to Arie van der Kooij on the occasion of his sixty-fifth birthday, which coincides with his retirement as Professor of Old Testament at Leiden University. The twenty-four contributions, written by leading scholars in the field of Old Testament studies, focus on the Book of Isaiah within the context of Hebrew and ancient Near-Eastern writings, particularly those from the Neo-Assyrian period, as well as on the book's reception history , particularly in its Greek and Syriac translations. Together these studies offer a rich and original contribution to the study of the Book of Isaiah in its Hebrew, Aramaic, Assyrian, Greek, Syriac, and Dutch contexts